Effects of glycerol and glucose on docosahexaenoic acid synthesis in Aurantiochyrium limacinum SFD-1502 by transcriptome analysis. Issue 1 (3rd January 2023) - Zhang, Huaqiu; Zhao, Xiangying; Zhao, Chen; Zhang, Jiaxiang; Liu, Yang; Yao, Mingjing; Liu, Jianjun
Abstract: Docosahexaenoic acid (DHA) has numerous functions in adjusting the organic health and pragmatic value in medicine and food field. In this study, we compared glycerol and glucose as the only carbon source for DHA production by Aurantiochytrium . When the glycerol concentration was 120 g/L, the maximum DHA yield was 11.08 g/L, and the DHA yield increased significantly, reaching 47.67% of the total lipid content. When the cells grew in glucose, the DHA proportion was 37.39%. Transcriptome data showed that the glycolysis pathway and tricarboxylic acid cycle in Aurantiochytrium were significantly inhibited during glycerol culture, which promoted the tricarboxylic acid transport system and was conducive to the synthesis of fatty acids by acetyl coenzyme A; glucose as substrate activated fatty acid synthesis (FAS)pathway and produced more saturated fatty acids, while glycerol as substrate activated polyketide synthase (PKS)pathway and produced more long-chain polyunsaturated fatty acids. This laid a foundation for fermentation metabolism regulation and molecular transformation.